The Importance of Sports for Public Health: The Importance of Sports for Public Health - Abdullah, Mohamad Razali (International Journal of Health, Medicine, and Sports, 2023)
Sports have become an irreplaceable element in maintaining public health amidst today's modern challenges. In the sphere of increasingly busy lifestyles and unbalanced diets, the importance of exercise as a key pillar of public health is becoming increasingly relevant. This abstract summarizes the results of studies on the importance of exercise in maintaining public health from various perspectives. The main benefits of exercise for people's physical health include weight regulation, increased muscle and bone strength, and prevention of cardiovascular disease and type 2 diabetes. Through regular physical activity, the risk of obesity and related health problems can be suppressed. In addition, exercise also helps improve the function of the respiratory and digestive systems, making it key to a more physically fit society. Aspects of mental health are also inevitable in this context. Exercise has been shown to have a positive impact on people's mental well-being by stimulating the release of endorphins, stress-reducing hormones, anxiety, and depression. In an increasingly complex society, exercise is becoming an effective solution for treating mental health and improving quality of life. Sport not only affects individuals personally but also has significant social implications. Through participation in sports groups or teams, social interaction can be enhanced, community bonds strengthened, and positive values such as cooperation and fair play are emphasized. This has an impact on building strong character and connecting with a more socially healthy society. However, sports promotion does not go without challenges. Busy modern lifestyles often reduce the time for exercise, and access to adequate sports facilities is not always evenly distributed in all walks of life. Therefore, the role of governments, educational institutions, and communities in promoting sports has become very important. In conclusion, exercise has a crucial role in maintaining overall public health. Through its impact on physical, mental, and social health, sport becomes an effective tool in caring for people's well-being. By strengthening the promotion and integration of sport in everyday life, we can shape a healthier, happier, and more empowered society.